The impact of social capital on the performance of small micro enterprises - Analia, Devi; Syaukat, Yusman; Fauzi, Akhmad; Rustiadi, Ernan (Penerbit Universiti Kebangsaan Malaysia, 2020)
Social capital is an important for the performance of small micro enterprises. The objective of this study is to identify the effect of social capital in terms of trust, networks, and norms on the performance of small micro enterprises. The paper measures the performance of small micro enterprises from the aspects of output production, internal processes, and resource capabilities. The data was obtained from 150 snack businesses in Padang Regency, West Sumatra, Indonesia. The effect of social capital on the performance of SMEs was analyzed using SEM-PLS. The results show that social capital improves the performance of SME snack businesses. Thus, social capital consisting of trust, networks, and norms has a significant influence on the performance of small micro enterprises in terms of the output produced, internal processes, and resource capabilities.